The APSES Gene MrStuA Regulates Sporulation in Metarhizium robertsii - Yang, Wenjing; Wu, Hao; Wang, Zhangxun; Sun, Qian; Qiao, Lintao; Huang, Bo (Frontiers in Microbiology, 2018)
The APSES family of genes is a unique family of transcription factors with a basic helix-loop-helix structure (APSES: Asm1p, Phd1p, Sok2p, Efg1p and StuAp) that are key regulators of cell development and sporulation-related processes. However, the functions of the APSES family of genes in entomopathogenic fungi Metarhizium robertsii have not been reported. Here, we report the identification and characterization of the MrStuA gene, a member of the APSES family, in M. robertsii. The selected gene was identified as StuA in M. robertsii (MrStuA) because it contains two conserved sequences, an APSES-type DNA-binding domain and a KilA DNA-binding domain, and has the highest homology with the StuA in C-II clade of the APSES family. We found that the number of conidia produced by △MrStuA were 94.45％ lower than the wild type. Additionally, conidia became elongated shape, sporulation was sparse and phialide were slender in the mutant. In addition, transcription levels of two central regulators of asexual development, AbaA and WetA, were significantly reduced in the mutant; furthermore, the transcription levels of other sporulation related genes, such as Mpk, Phi, Med, Aco, Flu, and FlbD, also decreased significantly. We also show that the median lethal time (LT50) of the mutant increased by 19%. This corresponded to a slower growth rate and an earlier conidia germination time compared to wild strain. However, the resistance of the mutant to chemicals or physical stressors, such as ultraviolet radiation or heat, was not significantly altered. Our results indicate that MrStuA may play a crucial role in regulating sporulation, as well as virulence, germination, and vegetative growth, in M. robertsii. This study improves our understanding of the impact of the transcription factor StuA on sporulation processes in filamentous fungi, and also provides a basis for further studies aimed at improving sporulation efficiency of these fungi for use as a biocontrol agent.